The Career Development of African American Managers: Exploring the Significance of Social and Cultural Capital on Leveraging Diversity - Trammell L. Bristol; Elizabeth J. Tisdell (Adult Education Research Conference, 2008)
The purpose of this paper is to discuss the career development findings of a larger qualitative research study exploring the experiences of African American managers in Fortune 500 companies, and then to consider the implications for leveraging diversity, in HRD and adult education practice.
Keywords: leveraging diversity; African American managers; career development